A comprehensive investigation on the effect of internal heat exchanger based on a novel evaluation method in the transcritical CO2 heat pump system. (November 2021) - Qin, Xiang; Wang, Dingbiao; Jin, Zunlong; Wang, Junlei; Zhang, Guojie; Li, Hang
Abstract: With the increasing demand for environmental protection, CO2, as a natural refrigerant, has always been environmentally friendly and safe, which makes transcritical CO2 heat pump system attract more attention. The internal heat exchanger is employed to improve the performance of transcritical CO2 heat pump system to match the traditional heat pump circulation system. In this work, two evaluation methods are proposed, one is the actual operation thermal effectiveness of internal heat exchanger, the other is the actual increase rate of COP . Compared with the experimental results, the conclusions can be extracted that the actual increase rate of COP can effectively evaluate the impact of the internal heat exchanger on system performance. In addition, this research deeply analyzes the influence of the internal heat exchanger on exergy efficiency. The results show that the internal heat exchanger greatly reduces the exergy efficiency under the discharge pressure of 7310 kPa and the ambient temperature of 15 °C, and the difference value between the system with and without internal heat exchanger reaches 39%. However, the influence of the internal heat exchanger on exergy efficiency decreases with the increase of discharge pressure and ambient temperature, the minimum difference value is only 0.1% at 11000 kPa and 30 °C.